Development of Vocabulary in Boys and Girls from Early and Middle Childhood (Annual of the Faculty of Philosophy in Skopje, 2017)
This paper examines the differences in the development of vocabulary in boys and girls from early and middle childhood. The lexical development is one of the most significant aspects of language development. Important quantitative and qualitative changes in the lexical domain occur early in life, especially during the preschool years. The number of words in the vocabulary is increasing with age and words are becoming more complex. Research on the differences between boys and girls usually indicate that girls are more successful in this regard.The total number of respondents in this research is 222. In this sample, 110 are boys and 112 are girls. Respondents are divided into three age groups i.e. 3-4 years, 5- 6 years and 7-9 years. In each group, there are 74 respondents. The average age of the groups is 3.3 for the first, 5.3 for the second and 7.9 for the third age group. All respondents are Macedonians, Orthodox Christians, and the Macedonian language is the first language learned by the time of the survey.The results confirm the first two hypotheses according to which older respondents and girls have more developed vocabulary compared to the younger respondents and boys. There was no significant interaction effect of age and gender. The findings are further discussed in the context of the available theoretical and empirical findings, followed by conclusions.
Keywords: DEVELOPMENT OF VOCABULARY; GENDER; EARLY AND MIDDLE CHILDHOOD; DEVELOPMENTAL PSYCHOLINGUISTICS